Primary antiphospholipid syndrome with celiac and splenic artery thrombosis - Arun Kumar Alagesan; R., Kannan; V., Vikrannth; J., Raghav (International Journal of Advances in Medicine, 2023)
Antiphospholipid syndrome (APS) is an autoantibody mediated acquired thrombophilia characterized by recurrent arterial or venous thrombosis and or pregnancy morbidity. We describe a case of 32-year-old female who had a medical history of APLA presented with complaints of abdominal pain for 20 days. On evaluation, CT abdomen contrast revealed celiac and splenic artery thrombosis. She was successfully treated with IV unfractionated heparin, warfarin and antiplatelets.